Efficacy of Twin Heart Meditation in Enhancing Psychological Well-Being among Students of Secondary School Level in Pokhara, Nepal - Gurung, Laxmi; Maharjan, Rocky; Khadka, Binita; Lama, Anju; Rayamajhi, Anju; Acharya, Indira; Gurung, Sapana; Lakhe, Rajendra; KC, Sarita (Mangal Research Journal, 2024)
Twin Heart Meditation (THM) is a popularly used meditative practice which focuses on activating the heart and crown chakras. It is known for its potential to cultivate loving-kindness, compassion, and spiritual connection, thereby enhancing psychological well-being. This study evaluates the efficacy of THM in reducing psychological distress a secondary-level school students in Pokhara, Nepal. Employing a quasi-experimental single-group pretest-posttest design, the study involved 182 students from Sainik Awashiya Mahavidhyalaya, selected through convenience sampling procedure. The Depression Anxiety Stress Scale (DASS-21) and Ryff's Psychological Well-Being Scale (RPWBS) were administered to assess psychological well-being before and after a four-week THM intervention. Results demonstrated significant reductions in stress, anxiety, and depression, along with positive changes in select dimensions of psychological well-being. The results were organized into four main themes: stress and THM, anxiety and THM, depression and THM, and psychological well-being and THM. These findings suggest that integrating THM into educational settings could effectively promote mental health and ease psychological distress among students.